Influence of Xanthan gum on the engineering properties and microstructure of expansive soils - Ouyang, Miao; Zhang, Hongri; Wang, Guiyao; Li, Youjun; Song, Jianping (Frontiers in Materials, 2025)
The application of novel materials that enhance soil engineering properties while maintaining vegetation growth represents an innovative strategy for ecological protection engineering of expansive soil slopes. Laboratory tests, including wetting and drying cycle tests, direct shear tests, unconfined swelling ratio tests, and vegetation growth tests, were conducted to analyze the effects of xanthan gum on both engineering and vegetation-related properties of expansive soil. The feasibility of xanthan gum for soil improvement was systematically evaluated. The interaction mechanism between xanthan gum and expansive soil was elucidated through scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses. Results demonstrated that xanthan gum effectively inhibited crack development and strength loss. With increasing xanthan gum content, the crack area ratio decreased logarithmically by up to 58.62%, while cohesion increased by 82.96%. The unconfined swelling ratio exhibited a linear reduction, with a maximum decrease of 43.58%. Notably, xanthan gum accelerated seed germination rate but did not significantly affect long-term vegetation growth. Mechanistically, xanthan gum improved soil properties via two pathways: (1) forming bridging structures between soil particles to enhance cohesion and tensile strength; (2) filling soil voids and generating a polymer film to inhibit water-clay mineral interactions, thereby reducing hydration membrane thickness. These findings offer both theoretical insights and practical guidelines for applying xanthan gum in ecological protection engineering of expansive soil slopes.